The Utilization of Nutraceuticals and Phytochemical Compounds to Inhibit The Interaction of Spike-protein SARS-CoV-2 Virus and ACE-2 Receptor for COVID-19 Therapy (Literature Review) - Ferdinand, David; Hartanti, Lanny (International Journal of Applied Biology, 2023)
SARS-CoV-2 virus can cause Coronavirus disease 2019 (COVID-19). The interaction between spike protein and ACE2 receptor causes virus entry into the cells. The aim of this study was to review the utilization of nutraceutical and phytochemical agents to inhibit the interaction of spike protein envelope SARS-CoV-2 virus and ACE2 receptor. The data literature was retrieved from several databases such as Google scholar, Science direct, and PubMed. This study was conducted from September-October 2020. The review process was conducted based on PRISMA Guidelines.The results showed that nutraceuticals such as tuna peptides (EEAGGATAAQIEM), nisin, teicoplanin, zinc, propolis, Ganoderma lucidum, brown algae, and lectin have the potential to inhibit the interaction of spike protein SARS-CoV-2 virus and ACE2 receptor. Phytochemical compounds such as curcumin, luteolin, EGCG, hesperidin, resveratrol, saikosaponin, nicotianamine, procyanidin and the others also have the same. From this study, it can be concluded that nutraceuticals and phytochemical agents have potential benefits in COVID-19 treatment based on in silico study. However, we need further studies based on in vitro experiments and in vivo to ensure the effectivity of those nutraceutical agents.